Netralisasi Pers dalam Menyikapi Pemilu 2024 Ditinjau dari Perspektif Hukum dan Etika Profesi - Calvin Haposan Pangaribuan; Widodo Ramadhana; Rizky R. (Jurnal Hukum Lex Generalis, 2024)
This article aims to see how press neutrality is in responding to the 2024 election from the perspective of law and proffesional ethics. The press, as the fourth pillar of democracy, plays a role in educating the public and serves as a platform for the public to help oversee the democratic process. In practice, the press has an important role during elections, as it can provide information about the electoral process, allowing the public to have multiple references before voting. However, in the modern era, the neutrality of the press is increasingly being questioned due to the fact that many media company owners are also involved in politics. So, how do law and professional ethics view this. Understanding this issue is crucial for the public to know the true position of the press in elections. In the Press Law itself, there is no mention of the word “neutrality” but what exists is “independence”.